Promises, promises. (Economist, 2000)
On August 16, 2000, Novell, a veteran networking-software firm in Silicon Valley, announced bitterly disappointing results. This dredged up fears about the firm's viability and rumors that Novell it might be sold, possibly to IBM, or split up. All of this is somewhat unexpected, because until early 2000, the view on Wall Street was that the Novell's chief executive, Eric Schmidt, had engineered the successful turnaround of a firm that had appeared to be dying when he took over in March 1997. Schmidt is a former chief technology officer at Sun Microsystems, and he was the driving force behind Sun's Java programming language. The strategy adopted by Schmidt to transform Novell; why his intended transformation of the firm is proving to be much more difficult than was anticipated; signs that things are looking up for the company; and the possibility that Novell's management may be compelled to sell all or part of the firm if it cannot produce much better results within two or three quarters are considered.